Clinical Trial Metrics: The Complexity of Conducting Clinical Trials in North American Cancer Centers. Issue 1 (13th January 2021) - Lee, Carrie; Werner, Theresa L.; Deal, Allison M.; Krise-Confair, Cassandra J.; Bentz, Tricia Adrales; Cummings, Theresa M.; Grant, Stefan C.; Lee, Ashley Baker; Moehle, Jessica; Moffett, Kristie; Peck, Helen; Williamson, Stephen; et al.
Abstract : PURPOSE: Cancer clinical trials offices (CTOs) support the investigation of cancer prevention, early detection, and treatment at cancer centers across North America. CTOs are a centralized resource for clinical trial conduct and typically use research staff with expertise in four functional areas of clinical research: finance, regulatory, clinical, and data operations. To our knowledge, there are no publicly available benchmark data sets that characterize the size, cost, volume, and efficiency of these offices, nor whether the metrics differ by National Cancer Institute (NCI) designation. The Association of American Cancer Institutes (AACI) Clinical Research Innovation (CRI) steering committee developed a survey to address this knowledge gap. METHODS: An 11-question survey that addressed CTO budget, accrual and trial volume, full-time equivalents (FTEs), staff turnover, and activation timelines was developed by the AACI CRI steering committee and sent to 92 academic cancer research centers in North America (n = 90 in the United States; n = 2 in Canada), with 79 respondents completing the survey (86% completion rate). RESULTS: The number of FTE employees working in the CTOs ranged from 4.5 to 811 (median, 104). The median number of analytic cases (ie, newly diagnosed or received first course of treatment) reported by the main center was 3, 856. Annual CTO budgets ranged from 250, 000 to 23, 900, 000 (median, 8.2 million). The median trial activation time, based on 61 centers, was 167 days. The median number of accruals per center was 480 (range, 5-6, 271) and median number of trials per center was 282 (range, 31-1, 833). Budget and FTE ranges varied by NCI designation. CONCLUSION: The response rate to the survey was high. These data will allow cancer centers to evaluate their CTO infrastructure, funding, portfolio, and/or accrual goals as compared with peers. A wide range in each of the outcomes was noted, in keeping with the wide variation in size and scope of cancer center CTOs across the United States and Canada. These variations may warrant additional investigation.